The Effect of Problem Based Learning Teaching Method on Students’ Critical Thinking Skills in Physics Lesson at SMA Negeri 4 Singaraja - Ni Putu Ayu Lisniandila; I Wayan Santyasa; Iwan Suswandi (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2018)
The study aims to find the effect of problem based-learning method (PBL) on students’ critical thinking skills in a physics course at SMA Negeri 4 Singaraja. The study is a quasi-experiment study with a pretest-posttest nonequivalent control group design. The population of this study was 245 tenth graders majoring in science at SMA 4 Singaraja. The sample of this study was 67 students distributed to two different classes. The data were analyzed by using descriptive analysis and one-way analysis of covariance (ANCOVA). The result of the study shows that there was critical thinking skills gaps between the students using PBL and students using the direct instruction method (DIM). The average score of PBL group had higher average critical thinking skills score (posttest) then the MDI group, in which the scores of PBLM group were in adequate category (M = 54,84; SD = 14,50), meanwhile the scores of DIM group were in low category (M = 43,05; SD = 14,29).